PEMANFAATAN MATERIAL KAYU RAMAH LINGKUNGAN DALAM BANGUNAN GEDUNG BERDASARKAN PERATURAN MENTERI PEKERJAAN UMUM DAN PERUMAHAN RAKYAT NO. 02/PRT/M/2015 TENTANG BANGUNAN GEDUNG HIJAU JO. PERATURAN MENTERI NEGARA LINGKUNGAN HIDUP NO. 08 TAHUN 2010 TENTANG KRIT - entang nuryanto (Dialogia Iuridica, 2020)
One effort to apply the principle of environmentally sustainable development in buildings is to apply the concept of green buildings. One of the building materials that are widely used in the administration of buildings is wood. PUPR Ministerial Regulation No. 02 / PRT / M / 2015 concerning Green Building and LH Ministerial Regulation No. 08 of 2010 concerning Criteria and Certification of Green Buildings require the implementation of buildings to implement environmentally friendly wood materials. However, in reality, there are still buildings that are held and existing buildings that do not meet the green building requirements that have been determined by legislation, especially in the use of environmentally friendly wood materials. The method used in this study is normative juridical. Secondary data collection techniques. As well as the research specifications used are analytical descriptive. It was concluded that the utilization of environmentally friendly wood materials in buildings based on Ministerial Regulation PUPR No. 02 / PRT / M / 2015 concerning Green Building Building jo. Ministerial Regulation LH No. 08 of 2010 concerning Criteria and Certification of Green Buildings is considered ambiguous and cannot accommodate the legal needs of the use of environmentally friendly wood materials. Implementation of the use of friendly wood materials the environtment in office buildings in the city of Bandung has not fully implemented optimally.